Unveiling lives: A glimpse into the daily routines of individuals affected by leprosy in Malaysia using the walk-and-talk technique - Norana Abdul Rahman; Vaikunthan Rajaratnam; Ruth M. H. Peters; Mohamed Rusli Abdullah; Karen Morgan (Global Public Health)
Leprosy, though curable, continues to present physical and psychosocial challenges for those affected. This study explored how individuals affected by leprosy in Malaysia navigated daily life, societal expectations, and personal challenges through the walk-and-talk technique, a participant-led qualitative approach that fostered spontaneous storytelling and reflexivity. By guiding researchers through their environments, participants shaped the narrative, shifting power dynamics and enabling authentic dialogue. Six participants from Kelantan and Selangor shared their everyday activities, aspirations, and coping strategies. Video documentation was used as a supplementary tool to capture non-verbal cues and contextual interactions. Visual, auditory, and field data were transcribed and thematically analysed using NVivo 12, revealing key themes, including resilience and perseverance, employment and economic sustenance, stigma, family support, and community engagement. Work emerged as central to their well-being, fostering dignity and providing financial stability. However, self-imposed stigma limited social inclusion, while strong familial and community bonds provided crucial support. These findings highlighted the effectiveness of the walk-and-talk technique in capturing rich qualitative data and emphasised the need for tailored interventions to address stigma, enhance social inclusion, and support the well-being and economic stability of individuals affected by leprosy.